Permanency and the Educational and Economic Attainment of Former Foster Children in Early Adulthood - Berger, Lawrence (Am Sociol Rev, 2018)
Foster children are at disproportionate risk of adverse outcomes throughout the life course. Public policy prioritizes permanency (exiting foster care through reunification with birth parents, adoption, or legal guardianship) as means of promoting healthy development and wellbeing for foster youth, but little empirical evidence indicates that permanency, including its most preferred form—reunification—promotes positive outcomes. Using multi-system, statewide longitudinal administrative data, we employed logistic and mixed-effects regression to examine educational attainment and earnings among former foster youth in early adulthood. We included a variety of sociodemographic and economic controls to reduce selection bias. We found that youth who did not attain permanency (those who aged out of care) had significantly higher odds of graduating high school and enrolling in college than reunified youth and youth who exited to guardianship, and similar odds as adopted youth. Earnings were similar across groups. Among aged-out (but not reunified) youth, odds of high school graduation and average earnings were higher for those who spent more time in foster care prior to age 18. Notably, some findings were sensitive to the categorization of youth who ran away from care. Overall, results suggest that permanency alone is insufficient to promote foster youths’ educational and economic attainment.